2008
DOI: 10.1590/s0103-84782008005000081
|View full text |Cite
|
Sign up to set email alerts
|

Temperatura e enriquecimento ambiental sobre o bem-estar de coelhos em crescimento

Abstract: II RESUMO O efeito da temperatura e o efeito do enriquecimento do piso de gaiola sobre o bem-estar de coelhos em crescimento foram avaliados. Quarenta e oito coelhos do grupo genético Botucatu, desmamados aos 35 dias de idade

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 4 publications
(4 reference statements)
1
4
0
4
Order By: Relevance
“…This result also corroborates those reported in previous studies in rabbits using other types of environmental enrichment, such as litter straw (SILOTO et al, 2009), wooden stick (VERGA et al, 2004, and hay and grass-cubes (LIDFORS, 1997); indicating that offering environmental enrichment for rabbits kept in cages can improve their welfare, as confirmed by reduction in the expression of abnormal behaviors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result also corroborates those reported in previous studies in rabbits using other types of environmental enrichment, such as litter straw (SILOTO et al, 2009), wooden stick (VERGA et al, 2004, and hay and grass-cubes (LIDFORS, 1997); indicating that offering environmental enrichment for rabbits kept in cages can improve their welfare, as confirmed by reduction in the expression of abnormal behaviors.…”
Section: Discussionsupporting
confidence: 91%
“…Enrichment allows the animal to express part of their behavioral repertoire, and also reduce the stress caused by the lack of space or poor environment that usually results in inactivity (JORDAN et al, 2006;BARROS, 2011). Most enrichment studies described physical changes in the rabbits' environment (VERGA et al, 2004;PRINCZ, 2008;SILOTO et al, 2009), but few studies have reported the availability of food enrichment, which can be an easy alternative to apply and with low cost (LIDFORS, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Using straw as cage enrichment had positive effects on rabbit behavior by increasing the frequency of exploratory activities and decreasing stereotypes and self-grooming (Siloto et al, 2008). Straw on the cage floor, however, may favor feces accumulation and represent a sanitary risk.…”
Section: Introductionmentioning
confidence: 99%
“…Many times a species that needs a lot of space for transport is maintained in small cages or in ones that have too many animals, limiting movement and preventing natural behavioral manifestations (SILOTO et. al, 2009).…”
Section: Animals Are Capable Of Enduring Lowmentioning
confidence: 99%